2021
DOI: 10.1002/jcla.24151
|View full text |Cite
|
Sign up to set email alerts
|

Worldwide prevalence of microbial agents’ coinfection among COVID‐19 patients: A comprehensive updated systematic review and meta‐analysis

Abstract: Background To provide information about pathogens’ coinfection prevalence with SARS‐CoV‐2 could be a real help to save patients’ lives. This study aims to evaluate the pathogens’ coinfection prevalence among COVID‐19 patients. Method In order to find all of the relevant articles, we used systematic search approach. Research‐based databases including PubMed, Web of Science, Embase, and Scopus, without language restrictions, were searched to identify the relevant bacterial, fungal, and viral coinfections among C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 99 publications
(178 reference statements)
1
25
0
Order By: Relevance
“… 2 Infection with SARS‐CoV‐2 may alter the human's microbiota, which further may affect the immune system. 3 Based on a systematic review, 4 a high prevalence of pathogenic microorganism was found among COVID‐19 patients. Thus, a delayed detection of SARS‐CoV‐2 could also result in increased mortality and morbidity due to the possibility of coinfection of SARS‐CoV‐2 and other pathogens.…”
Section: Introductionmentioning
confidence: 99%
“… 2 Infection with SARS‐CoV‐2 may alter the human's microbiota, which further may affect the immune system. 3 Based on a systematic review, 4 a high prevalence of pathogenic microorganism was found among COVID‐19 patients. Thus, a delayed detection of SARS‐CoV‐2 could also result in increased mortality and morbidity due to the possibility of coinfection of SARS‐CoV‐2 and other pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Case severity, morbidity, and mortality are affected by age, individual physiology, and pre-existing chronic conditions such as diabetes and hypertension. Moreover, microbial coinfections alter the disease pathophysiology and affect the recovery outcomes of patients [ 14 ]. Bacterial and fungal co-infections have been reported during previous influenza pandemic outbreaks.…”
Section: Introductionmentioning
confidence: 99%
“…were the main causative agents. Co-infections further increased morbidity and mortality rates [ 14 , 15 , 16 , 17 , 18 ]. Likewise, severely and critically ill COVID-19 patients with COVID pneumonia or developing ARDS are reported to be particularly vulnerable to bacterial and fungal superinfection, especially those hospitalized in an ICU on invasive or non-invasive ventilation [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“… 3 Mass testing against SARS‐CoV‐2 and in some circumstances alone with other bacterial, viral, or fungal microbiota is also encouraged for a wide range of COVID‐19 control measures, such as screening for community transmission 4 and evaluation for disease progression of COVID‐19 patients with/without coinfection of other microbial agents. 5 , 6 , 7 , 8 …”
Section: Introductionmentioning
confidence: 99%
“…3 Mass testing against SARS-CoV-2 and in some circumstances alone with other bacterial, viral, or fungal microbiota is also encouraged for a wide range of COVID-19 control measures, such as screening for community transmission 4 and evaluation for disease progression of COVID-19 patients with/without coinfection of other microbial agents. [5][6][7][8] Pooling of clinical specimens for mass detection of SARS-CoV-2 by nucleic acid testing has been reported to be effective in increasing diagnostic capacity with sufficient accuracy [9][10][11] for prompt disease intervention, especially when the prevalence of infected cases is low. In Taiwan, routine diagnosis of COVID-19 among individuals with suspected disease is conducted through a comprehensive nationwide SARS-CoV-2 laboratory network that comprises a total of 245 clinical laboratories at regional hospitals and medical institutions with a maximum daily capacity of 149,660 tests as of September 27, 2021.…”
mentioning
confidence: 99%